Chemical Biology Screening Identifies a Vulnerability to Checkpoint Kinase Inhibitors in TSC2-Deficient Renal Angiomyolipomas - Vaughan, Robert M.; Kordich, Jennifer J.; Chan, Chun-Yuan; Sasi, Nanda K.; Celano, Stephanie L.; Sisson, Kellie A.; Van Baren, Megan; Kortus, Matthew G.; Aguiar, Dean J.; Martin, Katie R.; MacKeigan, Jeffrey P. (Frontiers in Oncology, 2022)
Tuberous sclerosis complex (TSC) is a rare genetic syndrome and multisystem disease resulting in tumor formation in major organs. A molecular hallmark of TSC is a dysregulation of mammalian target of rapamycin (mTOR) through loss-of-function mutations in either tumor suppressor TSC1 or TSC2. Here, we sought to identify drug vulnerabilities conferred by TSC2 tumor suppressor loss through cell-based chemical biology screening. Our small molecule chemical screens reveal a sensitivity to inhibitors of checkpoint kinase 1/2 (CHK1/2), regulators of cell cycle and DNA damage response, in both in vitro and in vivo models of TSC2-deficient renal angiomyolipoma (RA) tumors. Further, we performed transcriptional profiling on TSC2-deficient RA cell models and discovered these recapitulate some of the features from TSC patient kidney tumors compared to normal kidneys. Taken together, our study provides a connection between mTOR-dependent tumor growth and CHK1/2, highlighting the importance of CHK1/2 inhibition as a potential anti-tumor strategy in TSC2-deficient tumors.